Shortcomings of the controlled foreign company legislation concerning foreign tax refund systems - Thomas Kollruss (PLoS ONE, 2026)
The aim of this study is to demonstrate that the CFC tax rules are legally ineffective in relation to those of foreign countries that operate a tax refund system at the shareholder level of the CFC (e.g., Malta). Under such a tax refund system, the CFC itself is highly taxed, but its shareholder receives a tax refund from the CFC’s country of residence upon profit distribution. Therefore, the research question is that the current CFC rules, owing to their legal structure, cannot effectively cover foreign countries of residence of the CFC that apply a tax refund system at the shareholder level. Using theoretical and legal research, this study shows that CFC taxation is largely ineffective in relation to foreign tax refund systems unless all of a CFC’s shareholders’ tax refunds are included in the calculation of the CFC’s tax burden. To illustrate this phenomenon, a comparative analysis of the CFC legislation in Germany, Austria and South Africa is conducted. The issue of foreign tax refund systems represents a significant challenge, as they have the potential to undermine the efficiency of CFC taxation as a pivotal instrument in the fight against tax avoidance. To solve this problem, a legal framework for the taxation of CFCs in countries with a tax refund system is being developed within this study to strengthen the taxation of CFCs and fight international tax avoidance. This study is a pioneering investigation of the legal efficiency of CFC taxation in the context of foreign jurisdictions that operate a tax refund system at the shareholder level of the CFC. It identifies the fundamental shortcomings of CFC tax law in the context of foreign tax refund systems and proposes legal solutions.